Determining the Effect of Covid-19 Disease on Family Physicians` Social and Daily Activities in Kayseri/Türkiye: - Afşin, Ahmet (Opšta medicina, 2022)
Objective: We aimed at determining the effects of Covid- 19 disease on family physicians` (FPs) daily work and life. Methods: We searched for GPs who had Covid-19 by making inquiries in the Medical Chamber, Association of GPs in Kayseri, and local health authorities. Our study period covers the first year of the Covid-19 pandemic in Türkiye (March 11th, 2020 – March 11th, 2021). The descriptive characteristics, we looked into, were the use of preventive measures, location of family health centers, the transmission route of Covid-19, the symptoms they experienced, FP’s general health status, and additionally details of isolation, diagnosis, and hospitalization procedures. Results: A total of 85 FPs (18.2% of all FPs in the Kayseri region) had Covid-19 in the first 12 months of the Covid- 19 pandemic in Kayseri/Türkiye. FPs who gave consent to participate in our study made up 60.8% of Kayseri`s FPs. Washing hands, keeping distance, using face masks, and frequent indoor ventilation were the most frequently used measures (>75%). More than 2/3 of FPs stuck to the preventive measures. The most frequent symptoms experienced by the FPs were muscle and joint pain, weakness, and fever (more than 1/5 of FPs, respectively 35.4%, 30.4%, 29.1%). The transmission sites were mostly Family Health Centers. Conclusion: About 1/6 of FPs were infected with Covid- 19. Almost all of them were working in the urban area. The mean hospitalization stay was 7.7 days and in more than 50% the symptoms of fever and cough were detected. The disease transmission was the most prevalent at the workplace and the most common concern of FPs was the protection of their families.